A STUDY OF PRECEDING NOUNS, SENTENCES AND TEXTS AS MEDIA TEXT UNITS (Scientific journal of the Fergana State University, 2025)
This article presents an idea about the intersection of the media, national language and national culture and the emergence of a new linguistic phenomenon at this point, namely, precedent units. The study of precedent units in Uzbek and world linguistics, their realization in speech in the form of a precedent name, a precedent sentence and a precedent text, as well as their specific features are discussed. Any scientific theories presented are substantiated by practical examples.